Factors Influencing The Intention To Use Mobile Health In Small Cities In China - Zhu, Fei (2023)
In spite of the swift advancement of mobile health in China lately, its adoption remains limited in small cities. Prior research predominantly cantered on large cities, with minimal attention given to small city contexts within China. Hence, this study seeks to develop a comprehensive conceptual framework encompassing technological attributes, individual traits, and societal contextual elements. Its goal is to elucidate key determinants impacting users' intent to adopt mobile health services within China's small cities. This study gathered data from 319 potential users via the Cradmo platform and employed PLS-SEM to authenticate both the model and hypotheses. The findings indicate that the intention of mobile health usage among users in China's small cities is positively and substantially affected by their attitudes in terms of personal traits. Additionally, social influence and facilitating conditions within the social context, along with performance expectancy associated with technological attributes, play vital roles. The attitude factor was notably and positively impacted by perceived severity and perceived vulnerability. Moreover, eHealth literacy played a positive moderating role in the connection between performance expectancy and usage intention. This study's outcomes contribute to theoretical advancements for future research endeavors. Additionally, the results offer pertinent suggestions to stakeholders involved in mobile health services.